2012
DOI: 10.1037/a0026652
|View full text |Cite
|
Sign up to set email alerts
|

Early androgen effects on spatial and mechanical abilities: Evidence from congenital adrenal hyperplasia.

Abstract: There is considerable controversy about the origins of sex differences in cognitive abilities, particularly the male superiority in spatial abilities. We studied effects of early androgens on spatial and mechanical abilities in adolescents and young adults with congenital adrenal hyperplasia (CAH). On tests of 3D mental rotations, geography, and mechanical knowledge, females with CAH scored higher than their unaffected sisters, and males with CAH scored lower than their unaffected brothers. Exploratory regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 82 publications
(104 reference statements)
5
66
1
1
Order By: Relevance
“…There is a theory that during the prenatal period, having an opposite-sex co-twin can change the level of prenatal testosterone, resulting in differentiated brain structure and masculinization of girls (Tapp et al, 2011;Ahrenfeldt et al, 2015). This means that girls from opposite-sex pairs are more likely to pursue activities linked to the development of spatial abilities (Berenbaum et al, 2012;Constantinescu & Hines, 2012) and have fewer differences from boys in mathematical ability and mathematical achievement (as found in our study). Thus, biological factors related to the formation of mathematical ability could be linked with sex differences as well.…”
Section: Discussionsupporting
confidence: 60%
“…There is a theory that during the prenatal period, having an opposite-sex co-twin can change the level of prenatal testosterone, resulting in differentiated brain structure and masculinization of girls (Tapp et al, 2011;Ahrenfeldt et al, 2015). This means that girls from opposite-sex pairs are more likely to pursue activities linked to the development of spatial abilities (Berenbaum et al, 2012;Constantinescu & Hines, 2012) and have fewer differences from boys in mathematical ability and mathematical achievement (as found in our study). Thus, biological factors related to the formation of mathematical ability could be linked with sex differences as well.…”
Section: Discussionsupporting
confidence: 60%
“…The capacity of androgens to modify spatially relevant regions of the CNS in laboratory animals (Isgor and Sengelaub, 2003) supports the possibility that spatial function in humans too is organized by androgens. A few studies have reported superior performance by females with CAH relative to controls on mental rotation tasks, figural disembedding, or learning the layout of a virtual environment (Resnick et al, 1986;Hampson et al, 1998;Mueller et al, 2008;Berenbaum et al, 2012), but these data are controversial because other studies have failed to find an effect on spatial abilities (Baker and Ehrhardt, 1974;McGuire et al, 1975;Helleday et al, 1994) or have even found lower scores in CAH samples (Perlman, 1973). Hines et al (2003) reported that females with CAH outperformed unaffected female relatives on throwing projectiles at targets, but showed no difference on tests of mental rotation.…”
mentioning
confidence: 98%
“…For instance, females with CAH have been found to show enhanced (more male-typical) knowledge of geography [57], knowledge that can only be acquired through experience. Thus, androgen exposure appears to affect this outcome via psychosocial influences.…”
Section: Gender Development In Individuals With Dsdmentioning
confidence: 99%